Indeks Massa Tubuh terhadap Tekanan Darah pada Petugas Memadamkan Kebakaran - Remita Ully Hutagalung (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This research aims to seek the relation of the index of the body with blood pressure on the fire-extinguishing officers in Samarinda. The method for this research is using a cross-sectional research design. The results of this statistical test indicate a significant link between the body mass index and hypertension but with a weak correlation. The correlation direction shows a positive direction, and it can be concluded that the higher body mass index is, the greater the degree of hypertension experienced by individuals. This research finds that the calculation of body mass index can be a predictor of the occurrence of hypertension, especially in individuals with excess weight up to obesity. The community is efficiently screening the risk of hypertension and supervision through the calculation of mass body index. The public does not need to rely on the availability of blood pressure gauges in screening. Similar research in various types of communities further strengthened that the body mass index is strongly correlated with hypertension. Keyword: Hypertension, Body Mass Index, Firefighter